2007
DOI: 10.2737/nrs-rb-20
|View full text |Cite
|
Sign up to set email alerts
|

Pennsylvania's Forest 2004

Abstract: In 2000, the Pennsylvania Department of Conservation's Natural Resources, Bureau of Forestry and the Northern Research Station's Forest Inventory and Analysis unit implemented a new annual system for inventorying and monitoring Pennsylvania's forests. This report includes data from 2000 to 2004. Pennsylvania's forest-land base is stable, covering 16.6 million acres or 58 percent of land area. More than 660,000 acres of forest land were lost from 1989 to 2004, mostly to residential or industrial development. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…McWilliams et al (2007) report that grasses, forbs, and rhizomatous ferns dominate Pennsylvania forest understories. In these conditions, there is very little relationship between percent cover and stem counts of a species by height class.…”
Section: Discussionmentioning
confidence: 99%
“…McWilliams et al (2007) report that grasses, forbs, and rhizomatous ferns dominate Pennsylvania forest understories. In these conditions, there is very little relationship between percent cover and stem counts of a species by height class.…”
Section: Discussionmentioning
confidence: 99%
“…The first comprehensive report for Pennsylvania using the new annual forest inventory system (Bechtold and others 2005) found that "the most disturbing finding from the forest inventory is the general lack of understory plants and tree regeneration across much of Pennsylvania." (McWilliams et al 2007). This finding was based on the Pennsylvania Regeneration Study (PRS) that had been ongoing since 2001.…”
Section: Speciesmentioning
confidence: 99%
“…Historical estimates of forest land area are available from FIA reports (Alerich et Distribution of Forest Land n Nonforest n Forest n Open water Total forest land 16,572,981 16,739,199 16,916,190 16 . 1993;Considine and Powell 1980;Ferguson 1958Ferguson , 1968McCaskill et al 2013;McWilliams et al 2007) and Illick (1923).…”
Section: What We Foundmentioning
confidence: 99%
“…For example, the cycle of plots measured from 2009 through 2014 are collectively labeled the 2014 inventory and were used to produce this 2014 report. The 2004 inventory was the first annual inventory to include the complete cycle of annual inventory plots (McWilliams et al 2007) and the 2009 inventory was the first annual inventory to include a complete remeasurement of plots (McCaskill et al 2013). This report for 2014 encompasses the second complete remeasurement of plots.…”
Section: Understanding Fia Datamentioning
confidence: 99%